2013
DOI: 10.1007/s12265-013-9526-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Streptococcal M-Protein Cardiopathogenic Epitopes in Experimental Autoimmune Valvulitis

Abstract: The M protein of rheumatogenic group A streptococci induces carditis and valvulitis in Lewis rats and may play a role in pathogenesis of rheumatic heart disease. To identify epitopes of M5 protein that produce valvulitis, synthetic peptides spanning A, B, and C repeat regions contained within the extracellular domain of the streptococcal M5 protein were investigated. A repeat region peptides NT4, NT5/6, and NT7 induced valvulitis similar to the intact pepsin fragment of M5 protein. T cell lines from rats with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 47 publications
2
53
0
Order By: Relevance
“…Comparison of the epitopes studied in humans with those found to induce valve lesions in the Lewis rat revealed that the GAS M protein epitopes were similar to those in the human and cross-reacted with cardiac myosin (1720). M protein specific T cell lines were found to home to the valve and induce VCAM-1 expression in a passive T cell transfer model (20).…”
Section: Introductionmentioning
confidence: 87%
“…Comparison of the epitopes studied in humans with those found to induce valve lesions in the Lewis rat revealed that the GAS M protein epitopes were similar to those in the human and cross-reacted with cardiac myosin (1720). M protein specific T cell lines were found to home to the valve and induce VCAM-1 expression in a passive T cell transfer model (20).…”
Section: Introductionmentioning
confidence: 87%
“…For instance, rat T cell lines that are specific for streptococcal M5 protein epitopes such as DKLKQQRDTLSTQKET 134 passively transfer valvulitis and upregulation of VCAM1 (REF. 135) to uninfected rats.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…This pathway may be crucial in induction of autoimmunity, which is a major pathogenic factor in cardiac damage. Group A streptococcus, the cause of rheumatic heart disease [40], andCVB3 [36] both induce CD4+ Tcell responses which cross-reactively recognize microbial and heart antigens and can adoptively transfer myocarditis to naive recipients.…”
Section: Myocarditis and Heart Failurementioning
confidence: 99%